2017
DOI: 10.1016/j.celrep.2017.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Integration of GPCR Signaling and Sorting from Very Early Endosomes via Opposing APPL1 Mechanisms

Abstract: SummaryEndocytic trafficking is a critical mechanism for cells to decode complex signaling pathways, including those activated by G-protein-coupled receptors (GPCRs). Heterogeneity in the endosomal network enables GPCR activity to be spatially restricted between early endosomes (EEs) and the recently discovered endosomal compartment, the very early endosome (VEE). However, the molecular machinery driving GPCR activity from the VEE is unknown. Using luteinizing hormone receptor (LHR) as a prototype GPCR for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
124
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(131 citation statements)
references
References 58 publications
(79 reference statements)
7
124
0
Order By: Relevance
“…We propose that these layers function together to determine the integrated cellular response these studies reported a second phase of GPCR and G protein activation in endosomes, with a brief (seconds to about a minute) refractory period separating the arrival of receptors in endosomes from the second activation phase. 46,53,54,56,57 Limitations of the present evidence. While there is now reasonable evidence that some GPCRs initiate G protein signaling after endocytosis, endomembrane signaling by G proteins is not proven and the present evidence supporting it has limitations and caveats.…”
Section: Layermentioning
confidence: 64%
See 1 more Smart Citation
“…We propose that these layers function together to determine the integrated cellular response these studies reported a second phase of GPCR and G protein activation in endosomes, with a brief (seconds to about a minute) refractory period separating the arrival of receptors in endosomes from the second activation phase. 46,53,54,56,57 Limitations of the present evidence. While there is now reasonable evidence that some GPCRs initiate G protein signaling after endocytosis, endomembrane signaling by G proteins is not proven and the present evidence supporting it has limitations and caveats.…”
Section: Layermentioning
confidence: 64%
“…13,37 Over the last decade, however, the hypothesis that GPCRs can initiate G protein-coupled signaling from endosomes as well as the plasma membrane has gained considerable experimental support. [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] Evidence for GPCR-G protein signaling from endosomes. Broadly considered, four experimental approaches have produced evidence supporting endosomal GPCR-G protein signaling.…”
mentioning
confidence: 99%
“…In addition to mediating GPCR forward transport, Rab43 may also play an important role in separating GPCRs from other plasma membrane proteins during maturation processing. Although GPCRs share a common structural topology and several proteins have been identified to control the sorting of GPCRs at the endosomal and lysosomal compartments after internalization, [155][156][157][158][159][160][161][162][163][164] how they are sorted from other plasma proteins at the ER level after their synthesis and then transported via specific routes are poorly understood. The Rab43-binding domain identified in the AT1R C-terminus was able to effectively convert the Rab43-independent transport of VSVG into Rab43-dependent transport, specifically from the ER to the Golgi.…”
Section: The Di-acidic Exe Motif and Er Exportmentioning
confidence: 99%
“…Other FSHR functions have been reported to be mediated by Gαi and Gαq proteins, the Gβγ dimer 12,13 and other molecules inducing proliferative signals under low FSHR density in the cell membrane 14 . FSHR-mediated activation of protein kinase B (AKT) occurs downstream of G protein activation [15][16][17] , and results in anti-apoptotic and proliferative activity in FSHR-expressing ovarian 18 and cancer 19 cells.…”
Section: Introductionmentioning
confidence: 99%
“…The FSHR forms heteromers with GPER. (A) Predicted structural model of the heterodimer between FSHR (green) and GPER1 (violet) seen in directions perpendicular (left)16 and parallel (right) to the bundle main axis. In this dimer, H6 of FSHR interacts with H7 ofGPER1 and H6 of GPER1 interacts with H7 of FSHR.…”
mentioning
confidence: 99%